2020
DOI: 10.1111/bjh.16730
|View full text |Cite
|
Sign up to set email alerts
|

SARS‐CoV‐2: a new aetiology for atypical lymphocytes

Abstract: Coronavirus disease 2019 (COVID-19) is an infectious disease caused by a newly emerging coronavirus, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). COVID-19 has a very variable clinical picture, ranging from asymptomatic to SARS that can lead to death.Our case, a 74-year-old female patient, presented with fever, moderate dyspnoea and leucocytosis (white blood cell count 21.6 9 10 9 /l, neutrophils 16.8 9 10 9 /l, lymphocytes 3.67 9 10 9 /l). Reverse transcriptase-polymerase chain reaction for SA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
35
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 0 publications
5
35
0
2
Order By: Relevance
“…We read with interest the recent paper by El Jamal and coworkers published in Pathology – Research & Practice [ 1 ] which reported that conspicuous atypical plasmacytoid lymphocytes are present in peripheral blood smears from patients with coronavirus disease 2019 (COVID-19), which is in line with other recent studies [ 2 , 3 ]. Indeed, many of the patients in these reports were critically ill and required intensive care therapy, and in one of the studies, similar cells were noted bronchoalveolar lavage fluid (BALF) [ 2 ].…”
supporting
confidence: 83%
“…We read with interest the recent paper by El Jamal and coworkers published in Pathology – Research & Practice [ 1 ] which reported that conspicuous atypical plasmacytoid lymphocytes are present in peripheral blood smears from patients with coronavirus disease 2019 (COVID-19), which is in line with other recent studies [ 2 , 3 ]. Indeed, many of the patients in these reports were critically ill and required intensive care therapy, and in one of the studies, similar cells were noted bronchoalveolar lavage fluid (BALF) [ 2 ].…”
supporting
confidence: 83%
“…These suggest that leucocyte counts, which are not more than the normal range, suspect COVID-19. Weinberg et al (2020) and Gérard et al (2020) observed atypical lymphocytes in patients with COVID-19. However, atypical lymphocytes have also been observed in patients with other infections.…”
Section: Discussionmentioning
confidence: 95%
“…So far, little is known on the clinical spectrum of ocular disease caused by SARS-CoV-2 infection. 13 , 14 However, several modes of transmission of SARS-CoV-2 involving ocular tissue and tears are being discussed. 9 11 The ACE-2 receptor has been found to be a binding site of SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 99%